Does authoritarianism necessarily stifle creativity? The role of discipline-focused authoritarian leadership - Zhao, Honglei; Su, Qingming; Lou, Ming; Hang, Chuqi; Zhang, Li (Frontiers in Psychology, 2022)
A burgeoning body of research has shown that authoritarian leadership have two characteristics of “light” and “dark”, for example it does not always have a negative impact on employees’ creative activities. However, there are not enough studies to explain this potential positive link. To extend the authoritarian leadership and creativity literatures, we draw on self-determination theory and event system theory, and elicit the two new notions of discipline-focused authoritarian leadership and appointment event criticality to examine whether, when, and how authoritarian leaders have a positive impact on employee creativity. With time-lagged data collected from 435 employees and their direct leaders in China, we found that discipline-focused authoritarian leadership has an indirect positive effect on employee creativity through creative self-efficacy. In addition, appointment event criticality strengthens the positive relation between discipline-focused authoritarian leadership and creative self-efficiency, and the indirect impact of discipline-focused authoritarian leadership on employee creativity through creative self-efficiency. Its theoretical and practical implications are discussed.